The Impact of Ovariectomy on Olfactory Neuron Regeneration in Mice. (3rd February 2020) - Yamada, Kentaro; Shiga, Hideaki; Noda, Takuya; Harita, Masayuki; Ishikura, Tomoko; Nakamura, Yukari; Hatta, Toshihisa; Sakata-Haga, Hiromi; Shimada, Hiroki; Miwa, Takaki
Abstract: Estrogen has been shown to affect differentiation and proliferation as a mitogen in various neural systems. Olfactory receptor cells are unique within the nervous system, and have the ability to regenerate even after an individual has reached maturity. Olfactory receptor cells also regenerate after experimentally induced degeneration. The purpose of this study is to observe the influence of estrogen depletion induced by ovariectomy on olfactory nerve regeneration. Female mice underwent bilateral ovariectomy at 8 weeks of age and received intraperitoneal administration of methimazole 1 week later. At 2, 4, and 6 weeks after methimazole administration, the olfactory mucosa was analyzed histochemically to determine olfactory epithelium (OE) thickness, olfactory marker protein distribution, and Ki-67 immunoreactivity. Furthermore, 2 weeks after ovariectomy, trkA protein distribution in the OE and nerve growth factor (NGF) levels in the olfactory bulb were determined by immunohistochemistry and enzyme-linked immunosorbent assay, respectively. Our results showed that in ovariectomized mice OMP, Ki-67, and trkA-immunopositive cells expression decreased at 2 weeks after methimazole injection, a time point at which regeneration is underway. At this same time point, although NGF production in the olfactory bulb had increased before methimazole administration, no differences were observed between the ovx and control groups. These results suggest that estrogen depletion induces a suppressive effect on regeneration of olfactory neurons, and that estrogen may have a potential use in the treatment of sensorineural olfactory dysfunction.